Análise Fitoquímica de Plantas do Ceará: potencial farmacológico de Cissus verticillata e composição volatil de Myrcia sp - Alexandre, Francisco Serra Oliveira (2007)
The present work reports on the volatile constituents from leaves and fruits of Myrcia sp. collected in Amontada County-Ceará State, in march/2006. It also reports on the phytochemical analysis of the decoction solution from fresh leaves, and the ethanol extract of dried leaves of Cissus verticillata in a concomitant study of its pharmacological potential as hipoglycemiant. GLC/MS and GLC/FID analysis of the essential oil from leaves (GAOFOLHAS) allowed the identification of 13 components: d-elemene, b-elemene, trans-caryophyllene, a-humulene, b-chamigrene, germacrene D, b-selinene, a-guaiene, a-selinene, a-Z-bisabolene, d-cadinene, epi-a-murolol and a-cadinol, while the essential oil from fruits (GAOFRUTOS) allowed the identification of 11 components: d-elemene, b-elemene, trans-cariophylene, a-guaiene, a-humulene, germacrene D, b-selinene, a-selinene, germacrene A, d-cadinene and germacrene B. The silica-gel chromatography analysis of the decoction solution of fresh leaves of C. verticillata allowed the separation of a fraction rich in tyramine, and from it, pure tyramine. Pharmacological tests on rats with aloxan-induced glycemia with both the tyramine rich fraction and pure tyramine allowed reduction on the glycemia levels, as well as for total cholesterol, triglycerids and VLDL, but HDL increasing. Silica-gel chromatography analyses of the ethanol extract from dried leaves of C. verticillata allowed the isolation of b-sitosterol and its glucoside derivative. Structure determination of all substances of C. verticillata was accomplished by means of spectroscopic techniques such as IR, 1H and 13C NMR, including uni and bi-dimensional pulse sequences (HMBC and HMQC) ad comparison with data from the literature.